Bankruptcy Reorganization through Markets : Auction-based Creditor Ordering by Reducing Debts (ACCORD) - Hausch, B. Donald (The World Bank, 1999)
November 1999 - Financial reorganization under bankruptcy reduces a firm's debts to serviceable levels through negotiations overseen by courts. Academics have suggested using markets for such negotiations, giving equity holders and junior claimants call options to buy the firm back from senior creditors. Hausch and Ramachandran further develop such a market-based approach for situations in which claimants are severely cash-constrained and there is good reason for existing owner-managers to remain in control. Under the ACCORD scheme - Auction-based Creditor Ordering by Reducing Debts - creditors remain creditors but form a queue, to be serviced in sequence from the firm's operating cash flows. Creditors bid for their position in this queue. Those accepting greater proportionate reductions in the face value of their claims (perhaps most pessimistic about the firm's prospects) are placed ahead of the others. A preexisting hierarchy of claims is honored by having claimants bid for their positions within the relevant segment of the queue. No one in the queue, including owners (who are last), is paid anything until the (reduced) debts of the first in line are fully discharged. The queue then moves up and the next claimant in line is serviced. Deferred creditors, who must wait their turn for the firm's operating cash surpluses, are not junior creditors in the conventional sense. Hausch and Ramachandran determine equilibrium bidding strategies, showing that the firm's aggregate debts would be reduced to a more serviceable level. This would improve the incentives of the firm's owner-managers, who remain in control, to operate the firm efficiently. Economic resources would thus be better used, and losses already incurred would be efficiently and quickly allocated among creditors.